The Semantic Significance of the Words of Sense in the Holy Qur’an: An objective study (Islamic Sciences Journal, 2023)
The senses are among the great blessings that God bestowed upon His creatures to deal with their surroundings in a way that makes them safe. No two differ in the importance of the senses or the senses for the human being through which he/she can differentiate between what benefits him and what harms him, and the Holy Qur’an has addressed the word sense to denote various meanings. According to the context in which the word is mentioned, the matter that prompted the people of interpretation to look closely at the diversity of the meanings of this word in its different contexts, and perhaps there were words that differ in their pronunciation, but they refer to the meaning of sense, for this reason the subject of sense enjoyed abundant interest by researchers to shed light on some The definitions of its meanings and standing in the stations of the aesthetic systems resulting from the texts that contained this word, for this reason the nature of the research required that it be on an introduction, two chapters and a conclusion.In the first topic, we dealt with the definition of sense in language and terminology, and an explanation of the types of senses in the Holy Qur’an.As for the second topic, it shows the significance of the sense of some meanings, and the indication of some words on the meaning of the sense in the Holy Qur’an..